Study of the Multi Particle Processes in Proton-Carbon and Deuteron-Carbon Interactions at 4.2 A GeV/c - Khan, A.; Suleymanov, M.K.; Wazir, Z.; Aslam, J. (The Nucleus, 2017)
In this paper, multi particle productions in hadron-nucleus and nucleus-nucleus interactions have been analyzed. The experimental data coming from 2m Propane Bubble Chamber, Joint Institute for Nuclear Research (JINR), Dubna, Russia has been used. The results have been compared with the simulated data from the Cascade Code. We could observe that the cascade code had problem in describing the experimental data for the multi particle events. One can conclude that the problem with the code could be connected due to production of ?-resonance and exclusion of collective phenomena in the Cascade code.